Notes on Costa Rican Opalinids. Il. Zelleriella antillensis ( Metcalf) and Z. bufoxena Metcalf - Ruiz, Armando (1959)
Four species of zelleriellae are known in Costa Rica, all described from local anurans. Zelleriella opisthocarya Metcalf, 1923, from Bufo coniferus Cope (collection place not indicated), Z. atelopyxena Metcalf, 1923, from Atelopus varius Stannius, collected at Pico Blanco, Z. dendrobatidis Metcalf, 1923, from Dendrobates tinctorius (Schneider), (collection place not indicated) and Zelleriella sp., a second species found by Metcalf in Atelopus varius but not named by this author, Unfortunately we have not had the opportunity of examining specimens of this frog so that we might encounter again the latter species of Zelleriella and proceed to redescribe it. With this note we increase the number of known species with the following: Z. antillensis (Metcalf, 1914) Metcalf, 1923 and Z. bufoxena Metcalf, 1923.